Root Canal Treatment of a Maxillary Second Premolar with Two Palatal Root Canals: A Case Report - Golmohammadi, Maryam; Jafarzadeh, Hamid (Iranian Endodontic Journal, 2016)
Accurate diagnosis of the root canal morphology and anatomy is essential for thorough shaping and cleaning of the entire root canal system and consequent successful treatment. This report describes a case of maxillary second premolar with two roots and three root canals (two mesial and distal palatal canals). The case report underlines the importance of complete knowledge about root canal morphology and possible variations, coupled with clinical and radiographic examination in order to increase the ability of clinicians to treat difficult cases. Keywords: Anatomical Variations; Maxillary Second Premolar; Root Canal Therapy